2009
DOI: 10.1089/ten.tea.2009.0038
|View full text |Cite
|
Sign up to set email alerts
|

The Microenvironment of Freeze-Injured Mouse Urinary Bladders Enables Successful Tissue Engineering

Abstract: Mouse bone marrow-derived cells implanted into freeze-injured bladder walls form smooth muscle layers, but not in intact walls. We determined if the microenvironment within injured urinary bladders was supportive of smooth muscle layer development. The urinary bladders of female nude mice were freeze-injured for 30 s. Three days later, the rate of blood flow in the wounded areas and in comparable areas of intact control urinary bladders was observed by charge-coupled device (CCD) video microscopy. Injured and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(49 citation statements)
references
References 45 publications
1
47
0
Order By: Relevance
“…To achieve clinically significant regeneration with these cells, it may be necessary to combine them with tissue engineering techniques that utilize scaffolds and/or growth factors. 43 In any case, our study clearly showed that in rabbits the injection of bone-marrow-derived cells accelerated the recovery of urinary sphincters compared to cell-free injections.…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…To achieve clinically significant regeneration with these cells, it may be necessary to combine them with tissue engineering techniques that utilize scaffolds and/or growth factors. 43 In any case, our study clearly showed that in rabbits the injection of bone-marrow-derived cells accelerated the recovery of urinary sphincters compared to cell-free injections.…”
mentioning
confidence: 49%
“…We believe that the distinct presence of myoblast-like cells at 14 days suggests that recovery of the muscle tissues might have stopped further development of the GFP-Pax7 double-positive myoblasts into striated or smooth muscle cells. 43 Understanding the controls for differentiation of the implanted cells is very important for the further development of regenerative medicine. While we do not understand the regulatory controls that govern the differentiation of the urethral striated and smooth muscle cells, it is clear that the presence of the myoblasts in the regenerated region may have important long-term significance.…”
mentioning
confidence: 99%
“…43 We do not yet know whether the urinary bladders that are damaged due to clinical radiotherapy have a suitable microenvironment for bone marrow-derived cell growth and differentiation. A further clinical complication is that radiotherapy often induces more serious damage, including loss of bladder tissues, bladder shrinkage with fibrosis, and synechia between urinary bladders and intestines.…”
Section: Discussionmentioning
confidence: 99%
“…Imamura et al . have reported that bone marrow derived MSC differentiated into smooth muscles in the rat urinary bladder 14,15 . More recently, Lin et al .…”
Section: Introductionmentioning
confidence: 97%